Senior High School Students' Knowledge and Attitudes Toward Information on Their Health in the Kumasi Metropolis - Boateng, Simon; Baah, Akosua; Boakye-Ansah, Doris; Aboagye, Bosco (Frontiers in Public Health, 2022)
The study examines Senior High School Students’ understanding and Attitudes toward Information on their health in the Kumasi Metropolis. Multiple sampling techniques (Convenient and simple random sampling techniques) were used in the study. Questionnaire was used to collect data from 391 respondents for the study. Frequencies and percentages were used to analyze the socio-demographic data. Again, the study used Pearson’s Correlation Coefficient to show the degree of relationship among level of knowledge of health information, attitudes towards seeking and sharing of health information. The study found students’ knowledge in the causes and symptoms of malaria, cholera and STIs to be appreciably high as a result of readings from textbooks and health professionals. Again, the study found that the students preferred sharing their health information with friends than their parents and schools’ authorities. The study further found that the major sources of students’ health information included health professionals and textbooks. Lastly, even though some of the students claimed internet sources to their health information, it was not a major source to the student body at large. The study recommends strong health systems on the campuses of Senior High Schools as they have become communities on their own as a result of the emergence of the free Senior High School Programme. Monitored Positive Peer-counselling Group should also be encouraged by the Schools’ management and by extension the Counselling Units for the students to share views on themselves, particularly on health issues where they deem fit.